2016
DOI: 10.1186/s12936-016-1418-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of seasonal malaria chemoprevention in upper west region of Ghana

Abstract: BackgroundIn Ghana, malaria is endemic and perennial (with significant seasonal variations in the three Northern Regions), accounting for 33 % of all deaths among children under 5 years old, with prevalence rates in children under-five ranging from 11 % in Greater Accra to 40 % in Northern Region. Ghana adopted the WHO-recommended Seasonal Malaria Chemoprevention (SMC) strategy with a trial in the Upper West Region in 2015. The objective of this study was to estimate the cost-effectiveness of seasonal malaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 27 publications
1
52
1
Order By: Relevance
“…shown to signi cantly reduce malaria in under 5 children participating in the mass drug administration program in different areas of diverse malaria transmission intensity (14)(15)(16)(17). Some economic bene t has further been attributed to seasonal malaria chemoprevention of all under 5 children (16,18), with recommendation for this approach to be integrated into the health system in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…shown to signi cantly reduce malaria in under 5 children participating in the mass drug administration program in different areas of diverse malaria transmission intensity (14)(15)(16)(17). Some economic bene t has further been attributed to seasonal malaria chemoprevention of all under 5 children (16,18), with recommendation for this approach to be integrated into the health system in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Few data from programme-implementation settings have been published, but one recent observational study in Mali in 2014 showed that prevalence of parasitaemia at the end of the high transmission seasonal was lower in areas receiving SMC (18%) than in areas not receiving SMC (46%) [ 14 ]. For recipients, data from clinical trials suggested high levels of community acceptability when taken during the peak malaria season [ 15 ], and at least one study from a programme implementation setting has shown a reasonable cost-effectiveness of the strategy (approximately US $100 per case averted and $3300 per under-5 death averted) [ 16 ], but broader data have yet to be published.…”
Section: Introductionmentioning
confidence: 99%
“…A door-to-door approach was employed in this study. Experience with different modes of delivery is being gained 12 , 13 and evaluations are being undertaken through the ACCESS-SMC project 14 . Delivery through fixed points has been less effective than delivery door to door.…”
Section: Discussionmentioning
confidence: 99%